2015
DOI: 10.1016/j.invent.2014.12.001
|View full text |Cite
|
Sign up to set email alerts
|

A feasibility open trial of guided Internet-delivered cognitive behavioural therapy for anxiety and depression amongst Arab Australians

Abstract: The present study examined the preliminary efficacy and acceptability of a culturally modified therapist-guided cognitive behaviour therapy (CBT) treatment for Arab Australians, aged 18 years and over with symptoms of depression and anxiety. To facilitate ease of use, the treatment was delivered via the Internet (Internet CBT; iCBT). Eleven participants with at least mild symptoms of depression (Patient Health Questionnaire 9-item (PHQ-9) total scores N 4 ) or anxiety (Generalised Anxiety Disorder 7-item (GAD-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 36 publications
(43 reference statements)
5
42
0
Order By: Relevance
“…The platform has been designed having in mind all the security requirements for online treatments, from the physical infrastructure to the software development. These requirements in Sweden are quite similar to the ones in other countries (Bennett, Bennett, & Griffiths, 2010;Kayrouz et al, 2014):…”
Section: Design and Securitysupporting
confidence: 68%
“…The platform has been designed having in mind all the security requirements for online treatments, from the physical infrastructure to the software development. These requirements in Sweden are quite similar to the ones in other countries (Bennett, Bennett, & Griffiths, 2010;Kayrouz et al, 2014):…”
Section: Design and Securitysupporting
confidence: 68%
“…Before intervention, groups did not differ in age (F [2,91] 40, p<0.05). While there were no significant group differences for any dimension, rANCOVAs showed significant group × time interaction effects for depression (BDI-II) and resilience (RS-11; Table 1).…”
Section: Resultsmentioning
confidence: 96%
“…Cognitive-behavioral therapy (CBT) has been shown to be very helpful in a variety of mental disorders [1]. Although CBT in an internet-based setting (I-CBT) is a comparatively new treatment approach, various studies and reviews point to its efficacy in decreasing symptoms of for example depression [2][3][4], anxiety disorders [5][6][7], insomnia [8] or posttraumatic stress disorder [9]. Moreover, there is growing evidence for a similar effectiveness of I-CBT compared to faceto-face CBT (FTF-CBT) for a broad variety of psychiatric and somatic disorders [10].…”
Section: Introductionmentioning
confidence: 99%
“…While the use of such interventions has considerable meta-analytic support in predominantly Western samples (e.g., Andersson et al, 2014 , Andrews et al, 2010 , van Ballegooijen et al, 2014 ), there is emerging evidence to indicate their potential in Arab populations. For example, several small but promising trials have recently demonstrated that Arab people can benefit from iCBT interventions ( Kayrouz et al, 2015 , Knaevelsrud et al, 2015 , Wagner et al, 2012 ). Among these, Knaevelsrud et al (2015) provided therapist-guided online treatment for Iraqis ( n = 47) with Post-Traumatic Stress Disorder (PTSD) and reported that 62% of those in a treatment group had recovered from post-traumatic stress symptoms at post-treatment, and that gains were maintained at three month follow up.…”
Section: Introductionmentioning
confidence: 99%